IMPORTANCE OF RESEARCH AND DRAFTING IN THE SCIENTIFIC PRODUCTION OF THE HEALTH AREA - Vallejo, MGS. Alida; Ramirez, Marjorie; Gurumendi, Ingrid; Perdomo, Tania (International Journal of Research -GRANTHAALAYAH, 2020)
Research increases human knowledge and enriches science, generating progress, quality of life, health, innovation, hence the importance of promoting it at all educational levels. Higher education institutions must implement the necessary strategies to improve communication skills, especially to improve the way of writing in order to share with the public the scientific findings that are inherent in the area of health in particular and of all science in general. The objective is to promote research to increase the production of scientific articles, with the socialization of knowledge in the area of health. Several factors influence this process. Scientific writing must complement the strengthening and interest of research, the publication of the results of the studies carried out must be shared with the entire society to benefit it and increase scientific production.